The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1302/0301-620x.87b11.16138
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of osteoarthritis after reconstruction of the anterior cruciate ligament

Abstract: We used single-photon emission computed tomography (SPECT) to determine the long-term risk of degenerative change after reconstruction of the anterior cruciate ligament (ACL). Our study population was a prospective series of 31 patients with a mean age at injury of 27.8 years (18 to 47) and a mean follow-up of ten years (9 to 13) after bone-patellar tendon-bone reconstruction of the ACL. The contralateral normal knee was used as a control. All knees were clinically stable with high clinical scores (mean Lyshol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
62
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(64 citation statements)
references
References 26 publications
1
62
0
1
Order By: Relevance
“…The prevalence of PTOA after ACL injury is conflicting because of the different classification methods for defining OA in the literature. 28 For patients with isolated ACL injuries, PTOA prevalence ranges from 0% to 39%, [29][30][31][32][33][34][35][36] whereas prevalence is higher among individuals with combined ACL and meniscal injuries (21%-100%). 31,34,[36][37][38] However, Oiestad et al 28 suggested that poor methodologic quality of studies has led to overestimation of PTOA rates and that prevalence may be closer to 13% in patients with isolated ACL injuries and between 21% and 48% in those with combined ACL and meniscal injuries who are at least 10 years postinjury.…”
Section: Risk Factors For Ptoa Joint Injurymentioning
confidence: 99%
“…The prevalence of PTOA after ACL injury is conflicting because of the different classification methods for defining OA in the literature. 28 For patients with isolated ACL injuries, PTOA prevalence ranges from 0% to 39%, [29][30][31][32][33][34][35][36] whereas prevalence is higher among individuals with combined ACL and meniscal injuries (21%-100%). 31,34,[36][37][38] However, Oiestad et al 28 suggested that poor methodologic quality of studies has led to overestimation of PTOA rates and that prevalence may be closer to 13% in patients with isolated ACL injuries and between 21% and 48% in those with combined ACL and meniscal injuries who are at least 10 years postinjury.…”
Section: Risk Factors For Ptoa Joint Injurymentioning
confidence: 99%
“…Blood-pool images of the ankles and the hindfoot were compared with those of the contra-lateral side, and graded from 0 to 2: grade 0, no increased radioisotope uptake; grade 1, minimal increased uptake; or grade 2, markedly increased uptake. This classification is a modification of the grading system used by Hart et al 19 for the examination of the knee joint. Delayed scintigraphy was performed 4.5 h after radioisotope injection.…”
Section: Radioisotope Scanmentioning
confidence: 99%
“…In the last decade magnetic resonance imaging (MRI) and computed tomography (CT) were increasingly used for evaluation of tunnel widening, as these promised higher accuracy and lower inter-or intra-observer variabilities 9,10,18,45 . Only few Authors have used bone scans, single-photon emission tomography (SPECT) or multi-modality imaging such as SPECT/CT to follow-up their patients after ACL reconstruction 11,13 . A variety of different algorithms and measurement methods using conventional radiographs, MRI or CT, whether in 2D or 3D have been described to evaluate bone tunnel widening 1-4, 6-10, 13, 15, 17-20, 22, 23, 26, 28-33, 37-47 .…”
Section: Introductionmentioning
confidence: 99%